Kajian Kegiatan Shadow Economy di Indonesia Dalam Novel Pulang Karya Tere Liye - Ellena Ratri Oktora; Fitriana Khusna Karima; Eva Dwi Kurniawan (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
The aim of this research is to explore the shadow economy in the Novel Pulang written which Tere Liye. The novel was analyzed using content analysis to find evidence and criticism of the shadow economy in the nation's economy, especially Indonesia. This research found that shadow economy is the main theme of this novel. Tere Liye very clearly defines the shadow economy and conveys to the reader what the shadow economy is all about become part of the world community, especially Indonesia. Not only that, GDP is an important indicator for measuring a country's economic performance. The research results show that the size of the shadow economy in Indonesia is still relatively high.